Desvendando a constituição subjetiva de uma professora : a história de Sofia - Baum, Virgínia Dornelles (2021)
This thesis is an case study that focuses on the subject of the subjective constitution of teaching and learning, according to the Theory of Subjectivity, by González Rey, which is associated with Qualitative Epistemology, by the same author. In this way, we seeks to answer the following problem: How are subjective configurations about teaching produced in the life story of a pedagogue recognized by her coworkers for developing a good job with the different ways of being and learning in the school context? Having as a general objective to produce a theoretical model that intends to build intelligibility about the problem. The Constructive-Interpretative Methodology was used. The main resources used to induce conversational systems were: insertion into the participant's work context (informal moments), a preliminary questionnaire and the use of images associated with life stages. The construction of the information was guided by the participant's life story, which allowed the thesis that teachers like Sofia, who live teaching in order to subjectively configure it as a power, as a possibility of building alternative subjective ways for the dialogic process, attribute value and meaning both to their pedagogical performance, to the processes of school learning and schooling, influencing new subjective productions, both in the individual and in the social sphere. Thus, the hypothetical construction is elaborated that teaching is an expression of Sofia's subjectivity, which is articulated around organizational cores, more or less stable, which represent the guiding principles of the participant's teaching, are named: the bond with the profession, flexibility, pedagogical humility and teaching ethics. In turn, each of these cores expresses, in a more or less evident way, Sofia's essential values, which are: affection, empathy, honesty and respect. In other words, the way Sofia conducts her teaching is articulated around values that (re)configure themselves throughout her life as principles. In this subjective production, affective memories are configured as legacies, which are closely associated with the value of the quality bond and school inclusion with effective learning. Evidencing the potential of dialogic education as a promoter of opportunities and mobility of social dynamics, a potential that is still little explored and, often, even opposed.